THE MAIN APPROACHES OF AUTOMATION OF THE PURCHASE PLANNING ON THE BASIS OF THE SYSTEM SAP R/З WITH REGARD TO WORKING CONDITIONS OF RUP «BMZ» - E. F. Terlejkaja (Литьë и металлургия)
The main approaches of purchase planning automation on the basis of the system SAP R/3 with regard to working conditions at RUP “BMZ” are examined.